Assistive and augmentive communication for the disabled intelligent technologies for communication, learning and teaching - Lau Bee Theng (Premier reference source, 2011)
"This book provides benefits to professionals and researchers working in various disciplines in the field, such as special education, healthcare, computational intelligence and information technology offering insights and support to individuals who are concerned with the development of children and adults with disabilities" - Provided by publisher